APLIKASI PENDATAAN BARANG INVENTARIS LAB KOMPUTER UNIVERSITAS CITRA BANGSA KUPANG BERBASIS WEB - Abraham Gerald Tibuludji; Dewi Anggraini; Heni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABRAHAM GERALD TIBULUDJI, Web-Based Inventory Data Collection Application for Citra Bangsa University Kupang Computer Lab. Supervised by DEWI ANGGRAINI and HENI.  Assets management or inventory management in the computer laboratory at Citra Bangsa University (UCB) Kupang which is still done manually with ledgers and spreadsheets has caused serious problems such as data inaccuracy, slow asset tracking, and loss of items, thus hampering operational effectiveness and accountability. Based on the literature review, a web-based information system solution with a Waterfall structured development methodology has proven effective in producing asset inventory application software that can improve the accuracy, efficiency, and transparency of inventory management. Therefore, this research aims to develop an integrated "Web-Based Inventory Data Collection Application for Citra Bangsa University Kupang Computer Laboratory", by utilizing a framework to produce a reliable, centralized, and real-time accessible system. This application is expected to transform conventional/manual systems into digital or computer-based systems, minimize errors, and provide fast and accurate information to support data-based decision making, thereby increasing transparency, accountability, and optimizing asset lifespan.